2021
DOI: 10.3390/metabo11050322
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission Governed by Drp1 Regulates Exogenous Fatty Acid Usage and Storage in Hela Cells

Abstract: In the presence of high abundance of exogenous fatty acids, cells either store fatty acids in lipid droplets or oxidize them in mitochondria. In this study, we aimed to explore a novel and direct role of mitochondrial fission in lipid homeostasis in HeLa cells. We observed the association between mitochondrial morphology and lipid droplet accumulation in response to high exogenous fatty acids. We inhibited mitochondrial fission by silencing dynamin-related protein 1(DRP1) and observed the shift in fatty acid s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
(65 reference statements)
3
10
1
Order By: Relevance
“…Interestingly, metformin inhibits Drp1 activity in peripheral tissues [47]. On the other hand, inhibition of Drp1 blunts mitochondrial fission and fatty-acid oxidation in fibroblasts under conditions of palmitate exposure [67]. Consistent with the ability of metformin to inhibit mitochondrial fission, we find here that the drug protected against shrinkage of average mitochondrial area in neurons exposed to palmitate, while liraglutide does not.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, metformin inhibits Drp1 activity in peripheral tissues [47]. On the other hand, inhibition of Drp1 blunts mitochondrial fission and fatty-acid oxidation in fibroblasts under conditions of palmitate exposure [67]. Consistent with the ability of metformin to inhibit mitochondrial fission, we find here that the drug protected against shrinkage of average mitochondrial area in neurons exposed to palmitate, while liraglutide does not.…”
Section: Discussionsupporting
confidence: 82%
“…In Sim1/MC4R neurons of the PVN, loss of MC4R is concomitant with fragmentation of mitochondrial network [7]. In vitro experiments have found that direct exposure to elevated palmitate induces fragmentation of mitochondria in insulinoma cells [46], podocytes [28], epithelial cells [67], and fibroblasts [68]. Similarly, we find here that direct exposure to elevated palmitate is sufficient to induce mitochondrial fragmentation and depolarization in hypothalamic neurons.…”
Section: Discussionsupporting
confidence: 77%
“…Many reports showed that mitochondrial morphology and mitochondrial metabolism interacted. For example, Song et al 43 inhibited mitochondrial fission by silencing Drp1 and found an increase in the fatty acid content of lipid droplets and a decrease in mitochondrial fatty acid oxidation, which clarified the role of mitochondrial dynamics in the control of intracellular fuel utilization and partitioning. The change of mitochondrial metabolism could model mitochondrial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that ceramides can modulate mitochondrial morphology through direct interaction with the fusion/fission machinery of mitochondrial membranes [ 26 ]. Transient morphological changes are necessary for a dynamic adaptation of mitochondrial (respiratory) function to a variety of metabolic cues, also to balance intracellular fuel utilization and partitioning [ 115 117 ]. It was initially observed that fatty acid turnover in cultured cells triggers mitochondrial fragmentation through increased de novo ceramide synthesis [ 118 ].…”
Section: Metabolic Roles Modes Of Action and Toxic Features Of Ceramidesmentioning
confidence: 99%